Highly porous metal organic framework derived NiO hollow spheres and flowers for oxygen evolution reaction and supercapacitors. Issue 3 (1st February 2021) - Reddy, B. Purusottam; Mallikarjuna, Koduru; Kumar, M.; Sekhar, M. Chandra; Suh, Youngsuk; Park, Si-Hyun
Abstract: In this study, metal-organic-framework (MOF) derived porous NiO hollow spheres and flowers were obtained using facile solvothermal synthesis and heat treatment. After pyrolyzing, the flower like and hollow spherical like morphology of NiO nanoparticles was successfully inherited from the initial MOF-based templates. The electrochemical studies demonstrated that the porous NiO hallow spheres unveiled a better supercapacitive performance (specific capacitance (Cs ) = 1058 F g −1 at current density (j) = 2 A g −1 ) and oxygen evolution reaction (OER) catalytic activity (overpotential (ɳ) = 323 mV) compared to porous NiO flowers (Cs  = 857 F g −1 at j = 2 A g −1 and ɳ = 346 mV). Moreover, excellent capacity retention of over 93% was obtained in porous NiO-hs nanoparticles even after 5000 cycles. The fabricated NiO//Fe2 O3 asymmetric supercapacitor delivered an energy density (E) of 35.75 W h Kg −1 under power density (P) of 780 W kg −1 and showed promising stability over 3000 cycles. Considering the ease of preparation and high catalytic activity and supercapacitive performance, these prous NiO hallow structures can be considered as a potential electrode material for next generation energy storage devices and OER catalysts. Graphical abstract: Image 1 Highlights: Highly porous metal organic frame work derived porous NiO hallow spheres and flowers were synthesized. NiO electrodes exhibited a capacitance of 1058 F g −1  at 2 A g −1  with 93% capacity retention even after 5000 cycles. NiO porous hollow structures displayed excellent OER catalytic activity with low overpotential of 323 mV. NiO//Fe2 O3  asymmetric device delivered a high energy density of 35.75 W h Kg −1  under power density of 780 W kg −1 .